2005
DOI: 10.1097/01.cji.0000164038.41104.f5
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of Pancreatic Carcinoma Cells to Enhance T Cell-Mediated Cytotoxicity Induced by Tumor Lysate-Pulsed Dendritic Cells

Abstract: Dendritic cells (DCs) can induce cytotoxic T-cell (CTL) responses against tumor antigens in vitro and in vivo, yet few cancer patients experience tumor regression after DC-based vaccination. Combination with other treatment modalities, such as radiation or pharmacologic anticancer agents, may reduce tumor cell resistance against immune responses. The authors tested whether treatment with gemcitabine or cyclooxygenase-2 (COX-2) inhibitors increases the sensitivity of pancreatic carcinoma cells to CTL-mediated k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Furthermore, promising therapeutic effects as well as safety and tolerance in a clinical phase I trial of the combination of VEGFR2-169 and gemcitabine have been reported for patients with advanced pancreatic cancer (32). Gemcitabine, a chemotherapeutic agent specific for pancreatic cancer, is reported to reduce the quantity of myeloid-derived suppressor cells and possibly augmented CTL-mediated antitumor immune responses in vivo (33)(34)(35). Moreover, a randomized clinical trial of cancer vaccine (ALVAC-CEA/B7.1 vaccine) combined with fluorouracil, leucovorin, and irinotecan showed that vaccine-mediated immunity was not affected by chemotherapy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, promising therapeutic effects as well as safety and tolerance in a clinical phase I trial of the combination of VEGFR2-169 and gemcitabine have been reported for patients with advanced pancreatic cancer (32). Gemcitabine, a chemotherapeutic agent specific for pancreatic cancer, is reported to reduce the quantity of myeloid-derived suppressor cells and possibly augmented CTL-mediated antitumor immune responses in vivo (33)(34)(35). Moreover, a randomized clinical trial of cancer vaccine (ALVAC-CEA/B7.1 vaccine) combined with fluorouracil, leucovorin, and irinotecan showed that vaccine-mediated immunity was not affected by chemotherapy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that DC vaccination of tumor bearing mice has led to increased tumor specific lysis by CD8 C T cells, expansion of IFNg secreting T cells, and tumor regression. [23][24][25] Targeting primary or metastatic lesions with intra-tumoral DC was effective in murine pancreatic cancer models and could be beneficial in human trials since a majority of patients are unresectable at the time of diagnosis. In one open label clinical trial, intra-tumoral injection of DC led to enhanced immunity and regression of tumor in several patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These findings open a novel field of investigations for future clinical trial design, taking into account the immunostimulatory capacity of chemotherapeutic agents such as gemcitabine, and using them in combined chemoimmunotherapy strategies in patients with pancreatic cancer (Correale, Aquino et al, 2003;Nowak, Lake et al, 2003a;Correale, Cusi et al, 2005;Dauer, Herten et al, 2005;Correale, Del Vecchio et al, 2008). Now the immunostimulatory effects of gemcitabine have been confirmed in patients with cancer.…”
Section: Combined Therapy Of Immunotherapy and Chemotherapymentioning
confidence: 99%
“…To induce efficient therapeutic CTL responses, crosspresentation of TAAs by DCs is essential. Treatment of pancreatic cancer cells and DCs with gemcitabine results in enhanced cross-presentation of TAAs by DCs, CTL expansion, and infiltration of the tumor, all of which are associated with augmented CTL (Nowak, Lake et al, 2003a;Nowak, Robinson et al, 2003b;Dauer, Herten et al, 2005;Correale, Cusi et al, 2005). A recent report that chemotherapeutic agents caused up-regulation of cationindependent mannose 6-phosphate receptor (CI-MPR) expression on cancer cells and a concurrent increase in the uptake of granzyme B by activated CTLs also strongly suggests chemotherapy can function in synergy with induction of CTL responses to cure established pancreatic cancer (Ramakrishnan, Assudani et al, 2010).…”
Section: Combined Therapy Of Immunotherapy and Chemotherapymentioning
confidence: 99%